Analysis of Sources of State Revenue from An Islamic Perspective - Wahyudi, Satya; Setiawati, Neng (Jurnal Prajaiswara, 2024)
Introduction/Main Objectives: This research aims to analyze the sources of state revenue from an Islamic perspective. Background Problems: Management of state revenue sources must be collected in the correct way and managed well and correctly in accordance with the objectives, namely for the welfare of the people and the benefit of the people, guided by the Al-Qur'an and the Hadith of Rasullah SAW Research  Methods: This research uses qualitative research methods through literature studies relating to the data and information needed regarding sources of state revenue from an Islamic perspective obtained from reference books, journals and other scientific works. Finding/Results : The research results show that Islam has determined sectors of state revenue, namely: Zakat, non-financial assets or wealth, which are obtained from ghanimah, fa'i, or amwal fahila, Dharibah, namely mandatory levies whose value is determined by the government, includes jizyah kharaj, ushr, nawaib, voluntary public acceptance, namely those whose objects and amounts are left to the payer. During the time of Rasulullah SAW, the main financial sources consisted of: (1) Jizyah. (2) Kharaj. (3) Ushr.     Conclusion : The application of state revenues originating from collection to the people must prioritize the principles of justice, keep away from everything that is usury and gharar, bring to the benefit of the people, maintain economic stability, transparency, and maintain compliance with community obligations.